The Internal Determinants of Financial Structure of Syrian Private Traditional Banks -Econometric Study using Panel Models - (Journal of Hama University, 2022)
This study aims to identify the internal determinants of financial structure for traditional private banks operating in Syria in the period between (2011-2019). The financial structure was expressed as a dependent variable, against each of the liquidity, change in operating income, asset, and dividend ratio, as independent variables. By applying the Random Effects Model (REM) of panel data, the results showed that all the studied variables constitute determinants of financial structure in Syrian banks, and that the order of the impact of these variables on financial structure in terms of the strongest was as follows: asset size with a positive effect, distributions with a positive effect, change in operating income with a negative effect, liquidity with a positive effect.
Keywords: Financial Structure of Banks, Debts, internal Determinants, Random Effects Model, Financial Leverage, Banks operating in Syria.